In vitro Assessment of Novel Bioactive Compounds’ Anti-Inflammatory and Wound-Healing Properties for Adjunctive Treatment of Oral Mucosal Lesions and Ulcerations - Saud Naif Albakri; Vivek Kumar Sidhu; M. Pradeep Reddy; Shiana Jo; Saloni Verma; D Anupama Prasad (Journal of Pharmacy and Bioallied Sciences)
Background: Oral mucosal lesions and ulcerations, prevalent in various dental and systemic conditions, frequently result in considerable discomfort and healing delays. This study evaluates the potential of rosiglitazone and apigenin as adjunctive treatments, focusing on their anti-inflammatory and wound-healing properties. Materials and Methods: A standardized three-dimensional human oral mucosal model was employed to assess the efficacy of rosiglitazone and apigenin. These compounds were applied in different concentrations and compared against a control group receiving no treatment. The primary outcomes measured were the reduction of inflammation, indicated by cytokine levels (IL-1β, TNF-α) via enzyme-linked immunosorbent assay (ELISA), and the rate of wound healing, evaluated through scratch assays and histological analysis over seven days. Results: Rosiglitazone exhibited a significant decrease in cytokine levels, with IL-1β and TNF-α reduced by 40% and 35%, respectively, at 200 μg/mL compared to the control. Apigenin showed a more pronounced reduction, decreasing both cytokines by 50% at a concentration of 250 μg/mL. In terms of wound healing, rosiglitazone and apigenin enhanced closure rates by 60% and 75%, respectively, significantly outperforming the control group, which exhibited only a 25% closure. Histological assessments confirmed increased cellular proliferation and reduced inflammatory infiltration in the treatment groups. Conclusion: Rosiglitazone and apigenin demonstrate significant anti-inflammatory and wound-healing effects, suggesting their potential utility as effective adjunctive treatments for oral mucosal lesions and ulcerations. These results support further clinical trials to verify their therapeutic efficacy and safety in human patients.